Sirt3 mediates reduction of oxidative damage and prevention of age-related hearing loss under caloric restriction - Someya, Shinichi; Yu, Wei; Hallows, William C; Xu, Jinze; Vann, James M; Leeuwenburgh, Christiaan; Tanokura, Masaru; Denu, John M; Prolla, Tomas A (Cell, 2010)
Caloric restriction (CR) extends the life span and health span of a variety of species and slows the progression of age-related hearing loss (AHL), a common age-related disorder associated with oxidative stress. Here, we report that CR reduces oxidative DNA damage in multiple tissues and prevents AHL in wild-type mice but fails to modify these phenotypes in mice lacking the mitochondrial deacetylase Sirt3, a member of the sirtuin family. In response to CR, Sirt3 directly deacetylates and activates mitochondrial isocitrate dehydrogenase 2 (Idh2), leading to increased NADPH levels and an increased ratio of reduced-to-oxidized glutathione in mitochondria. In cultured cells, overexpression of Sirt3 and/or Idh2 increases NADPH levels and protects from oxidative stress-induced cell death. Therefore, our findings identify Sirt3 as an essential player in enhancing the mitochondrial glutathione antioxidant defense system during CR and suggest that Sirt3-dependent mitochondrial adaptations may be a central mechanism of aging retardation in mammals.